August's Abusive Act Reflected In Sara Gruen's WaterFor Elephants Novel (2006): A Psychoanalytic Critisism - Prihtani, Ryan; , Drs. Abdillah Nugroho, M. Hum; , Siti Fatimah S.Pd, M.Hum (2013)
The research is proposed to analyze how August‟s abusive act reflected in Water for Elephants novel by Psychoanalytic Criticism. There are two objectives: the first is to analyze the novel based on its structural elements and technical elements, and the second is to analyze the main character's personality using a psychoanalytic approach. This study is a qualitative study, using Sara Gruen‟s Water for Elephant novel 2006 as of structural elements, and the secondary data. The primary data source is Water for Elephants novel which is written by Sara Gruen , and the secondary data are some articles, book of literary and internet related to the subject. The method of collecting data in this research is library research by reading some related books and articles, accessing internet, taking notes of important parts, arranging, and drawing conclusion the data. In analyzing the data, the writer employs descriptive analysis. The results showed that this novel illustrates how abusive towards fellow human beings will make us lose the people we love. One thing that can destroy human‟s dreams is abusive. Thus, in order to keep away from abusive acts is caring and loving people around.